This Week in Psychedelics - 9.14.18 (Think Wilder)
Cannabis Canadian Military Reveals New Rules Regarding Cannabis Use ( High Times ) Marijuana Use Is on the Rise Among Baby Boomers According to a New Study ( TIME ) Legal Canadian Marijuana Workers, Investors Will Be Treated Like Illegal Traffickers, Official Confirms ( Newsweek )